p53 as a biomarker and potential target in gastrointestinal stromal tumors - Wu, Chiao-En; Chen, Chiao-Ping; Huang, Wen-Kuan; Pan, Yi-Ru; Aptullahoglu, Erhan; Yeh, Chun-Nan; Lunec, John (Frontiers in Oncology, 2022)
KIT and PDGFRA play a major role in the oncogenic process in gastrointestinal stroma tumors (GIST) and small molecules have been employed with great success to target the KIT and PDGFRA pathways in this cancer. However, approximately 10% of patients with GIST are resistant to current targeted drug therapy. There is a need to explore other potential targets. Although p53 alterations frequently occur in most cancers, studies regarding p53 in GIST have been limited. The CDKN2A/MDM2/p53 axis regulates cell cycle progression and DNA damage responses, which in turn control tumor growth. This axis is the major event required for transformation from low- to high-risk GIST. Generally, p53 mutation is infrequent in GIST, but p53 overexpression has been reported to be associated with high-risk GIST and unfavorable prognosis, implying that p53 should play a critical role in GIST. Also, Wee1 regulates the cell cycle and the antitumor activity of Wee1 inhibition was reported to be p53 mutant dependent. In addition, Wee1 was reported to have potential activity in GIST through the regulation of KIT protein and this mechanism may be dependent on p53 status. In this article, we review previous reports regarding the role of p53 in GIST and propose targeting the p53 pathway as a novel additional treatment strategy for GIST.